Oxidation-assisted graphene heteroepitaxy on copper foil. Issue 44 (28th October 2016) - Reckinger, Nicolas; Tang, Xiaohui; Joucken, Frédéric; Lajaunie, Luc; Arenal, Raul; Dubois, Emmanuel; Hackens, Benoît; Henrard, Luc; Colomer, Jean-François
Abstract : We propose an innovative approach based on oxidation to synthesize aligned large-area single-crystalline monolayer graphene flakes by chemical vapor deposition on copper foil. Abstract : We propose an innovative, easy-to-implement approach to synthesize aligned large-area single-crystalline graphene flakes by chemical vapor deposition on copper foil. This method doubly takes advantage of residual oxygen present in the gas phase. First, by slightly oxidizing the copper surface, we induce grain boundary pinning in copper and, in consequence, the freezing of the thermal recrystallization process. Subsequent reduction of copper under hydrogen suddenly unlocks the delayed reconstruction, favoring the growth of centimeter-sized copper (111) grains through the mechanism of abnormal grain growth. Second, the oxidation of the copper surface also drastically reduces the nucleation density of graphene. This oxidation/reduction sequence leads to the synthesis of aligned millimeter-sized monolayer graphene domains in epitaxial registry with copper (111). The as-grown graphene flakes are demonstrated to be both single-crystalline and of high quality.